2000
DOI: 10.1021/ja9925251
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Synthetic Organic Reactions Using Supercritical Water:  Noncatalytic Beckmann and Pinacol Rearrangements

Abstract: A high-pressure and high-temperature FTIR was used to study noncatalytic Beckmann and pinacol rearrangements using supercritical water (scH 2 O). Significant acceleration of Beckmann and pinacol rearrangements can be achieved by using scH 2 O, especially near the critical point, even in the absence of any acid catalysts. It has been demonstrated that scH 2 O acts effectively in the place of conventional acid catalysts for both the rearrangements. The rate of pinacol rearrangement using scH 2 O is significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
85
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(88 citation statements)
references
References 61 publications
1
85
0
2
Order By: Relevance
“…It is well known that ketones are synthesized in the pinacol rearrangement of vicinal diols: for example, 2,3-dimethyl-2,3-butanediol, so-called pinacol, is converted into 3,3-dimethyl-2-butanone, pinacolone, through dehydration. Homogeneous acids such as SbCl 5 AgSbF 6 1 and BF 3 2 catalyze the rearrangement. It is reported that the rearrangement proceeds under supercritical conditions without catalyst.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that ketones are synthesized in the pinacol rearrangement of vicinal diols: for example, 2,3-dimethyl-2,3-butanediol, so-called pinacol, is converted into 3,3-dimethyl-2-butanone, pinacolone, through dehydration. Homogeneous acids such as SbCl 5 AgSbF 6 1 and BF 3 2 catalyze the rearrangement. It is reported that the rearrangement proceeds under supercritical conditions without catalyst.…”
mentioning
confidence: 99%
“…It is reported that the rearrangement proceeds under supercritical conditions without catalyst. 3 It is also reported that solid acids such as aluminum phosphate, 4,5 sulfated zirconia, 6 and zeolite 7 catalyze the rearrangement in the vapor phase. In the vapor-phase catalytic rearrangement, however, DMB can be produced as a by-product, into which pinacolone is transformed and dehydrated.…”
mentioning
confidence: 99%
“…However, Ni is widely used due to its affordability. Also at SCW conditions, H + and OH -ions are liberated at high concentrations which creates a perfect condition favorable to acid-base catalysts during the WGSR [32][33][34]. Therefore, alkaline homogeneous catalysts such as KOH, NaOH, K 2 CO 3 and Na 2 CO 3 can promote biomass gasification for effective H 2 production [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many important organic reactions such as secondary alcohol oxidation without an oxidant or a catalyst to generate carbonyl compounds and hydrogen gas [19], efficient non-catalytic Oppenauer oxidation of alcohols [20], and 4 the Beckmann rearrangement [21] have been performed under non-catalytic conditions in sub-CW and SCW. Regarding 2,6-and 4-alkylation of phenol in SCW, a pioneering work using aldehydes as a source of alkyl groups was reported by Adschiri et al; 2,6-and 4-alkylation of phenol showed much higher reactivity than methylation of phenol using supercritical methanol [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%